Challenges and coping strategies on spiritual integrating in counseling session among experienced and novice counsellors during Covid-19 pandemic outbreak - Sharif, Ikram; Ku Johari, Ku Suhaila; Kamal, Harizah; Fuad Mohd Karim, Dharatun Nissa (Abdullah Kuzu, 2021)
This study surveyed experienced and novice counsellors' perceptions of the spiritual element and examined its application, particularly in addressing mental health issues. The study is qualitative and employs a case study methodology. Four registered counsellors with more than ten years of experience participated in the study, as did four novice counsellors with less than three years of experience. For data collection, researchers rely on semi-structured interview techniques to achieve data saturation. Following that, the study findings were analyzed manually using a thematic method that began with open coding, progressed through category coding, and culminated in developing themes. The study's findings concluded that all participants agreed and frequently incorporated spiritual elements into counselling sessions, either directly or indirectly. Additionally, the researchers discovered that more experienced counsellors were more adapt at incorporating spiritual elements into their sessions than novice counsellors. This study aims to raise awareness about the efficacy of spiritual aspects in counselling sessions. Additionally, this study will provide an insight into the direction in which to improve the quality of counsellors to increase their credibility, which will help reduce mental health problems.